Sister novelists : the trailblazing Porter sisters, who paved the way for Austen and the Brontës - Looser, Devoney, 1967- (Bloomsbury Publishing, 2022)
"Before the Brontë sisters picked up their pens, or Jane Austen's heroines Elizabeth and Jane Bennet became household names, the literary world was celebrating a different pair of sisters: Jane and Anna Maria Porter. The Porters--exact contemporaries of Jane Austen--were brilliant, attractive, self-made single women of polite reputation who between them published twenty-six books and achieved global fame. They socialized among the rich and famous, tried to hide their family's considerable debt, and fell dramatically in and out of love. Their moving letters to each other confess every detail. Because the celebrity sisters expected their renown to live on, they preserved their papers, and the secrets they contained, for any biographers to come. But history hasn't been kind to the Porters. Credit for their literary invention was given to their childhood friend, Sir Walter Scott, who never publicly acknowledged his debt to their ideas. With Scott's more prolific publication and even greater renown, the Porter sisters gradually fell from the pinnacle of celebrity to eventual obscurity. Now, Professor Devoney Looser, a Guggenheim fellow in English Literature, sets out to re-introduce the world to the authors who cleared the way for Austen, Mary Shelley, and the Brontë sisters. Capturing the Porter sisters' incredible rise, from when Anna Maria published her first book at age fourteen in 1793, through to Jane's fall from prominence in the Victorian era, and then to the auctioning off for a pittance of the family's massive archive, Sister Novelists is a groundbreaking and enthralling biography of two pioneering geniuses in historical fiction"--